2014
DOI: 10.1007/s11103-014-0253-2
|View full text |Cite
|
Sign up to set email alerts
|

Activation tagging of ATHB13 in Arabidopsis thaliana confers broad-spectrum disease resistance

Abstract: Powdery mildew species Oidium neolycopersici (On) can cause serious yield losses in tomato production worldwide. Besides on tomato, On is able to grow and reproduce on Arabidopsis. In this study we screened a collection of activation-tagged Arabidopsis mutants and identified one mutant, 3221, which displayed resistance to On, and in addition showed a reduced stature and serrated leaves. Additional disease tests demonstrated that the 3221 mutant exhibited resistance to downy mildew (Hyaloperonospora arabidopsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 80 publications
2
24
0
Order By: Relevance
“…Biotic and abiotic factors alter the expression of a large number of transcription factors. For example, the A. thaliana homeodomain-leucine zipper (HD-Zip) transcription factor, ATHB13 influences resistance to both biotic and abiotic stresses (Gao et al, 2014;Cabello et al, 2012;Cabello and Chan, 2012).…”
Section: Plant Responses To Aphid Infestationmentioning
confidence: 99%
“…Biotic and abiotic factors alter the expression of a large number of transcription factors. For example, the A. thaliana homeodomain-leucine zipper (HD-Zip) transcription factor, ATHB13 influences resistance to both biotic and abiotic stresses (Gao et al, 2014;Cabello et al, 2012;Cabello and Chan, 2012).…”
Section: Plant Responses To Aphid Infestationmentioning
confidence: 99%
“…ATHB6 in Arabidopsis is up-regulated by water deficit conditions and exogenous application of abscisic acid (ABA), and functions as a crucial regulator of the ABA signal pathway possibly by interacting with downstream of ABI1 (S€ oderman et al, 1999;Himmelbach et al, 2002). The Arabidopsis ATHB13 is suggested to be involved in the regulation of cotyledon and leaf development as a component of the sucrosedependent signaling pathway, and also participates in the crosstalk between abiotic and biotic stress-responsive gene-expression networks (Hanson et al, 2001;Gao et al, 2014). Recent studies have shown that, in non-climacteric fruits, ABA is required for the regulation of ripening-related anthocyanin biosynthesis, and application of exogenous ABA induced accumulation of anthocyanins and flavonols in grape berries (Koyama et al, 2010;Jaakola, 2013).…”
Section: Promoter-protein Interactions In Planta and In Vitromentioning
confidence: 99%
“…AtHB23 has been described as being expressed in the adaxial region of leaves (Kim et al ., ), and also as being involved in hypocotyl elongation and cotyledon expansion under red light (Choi et al ., ). AtHB13 has a role in abiotic and biotic stress responses, pollen hydration and seed germination (Hanson et al ., , ; Cabello and Chan, ; Gao et al ., ; Ribone et al ., ; Silva et al ., ). Both AtHB13 and AtHB23 are involved in the inhibition of inflorescence stem elongation, which drives cell proliferation, although their roles are not redundant (Ribone et al ., ).…”
Section: Introductionmentioning
confidence: 98%